Assessing Early Behavioral Indicators of Tolerance in Infants Receiving Formula with Added Lactobacillus rhamnosus GG (LGG). (29th May 2020) - Gutierrez-Orozco, Fabiola; Harris, Cheryl; Wampler, Jennifer; Berseth, Carol Lynn
Abstract: Objectives: To evaluate the nutritive effects of an infant formula with added LGG on early behavioral indicators of tolerance in infants experiencing crying and fussing often associated with infantile colic. Methods: In this single-center, double-blind, controlled, parallel, prospective study, infants (14 to 28 days of age) determined to cry and/or fuss ≥3 hours/day for ≥3 days/week (in a one-week period) were randomized to receive one of two formulas over a 21-day feeding period: marketed partially hydrolyzed (PH) cow's milk-based infant formula (PH: n, 35) or a similar formula with added LGG (PH-LGG: n, 36). Parents/caregivers used a validated parent-report diary to record crying/fussing and awake/content behavior at three time points: Study Days 2–4 (baseline), Days 10–12, and Days 18–20 (Study End). The primary outcome, duration (hours/day) of crying/fussing (averaged over each three-day period), was analyzed by repeated measures, mixed-effects models. Results: Birth characteristics (sex, race, weight) and age (days; mean ± SE) at study entry (PH: 19.7 ± 0.8; PH-LGG: 19.3 ± 0.8) were similar for study groups. No group differences in mean study formula intake (g/day) or mean achieved weight (g) at any study time point were detected. Completion rates were similar through Day 21 (PH: n  = 33, 94%; PH-LGG: n  = 33, 92%). Duration of crying/fussing (mean ± SE) decreased over time with no significant differences detected in the PH vs PH-LGG group at Baseline (4.8 ± 0.3 vs 4.0 ± 0.3; P  = 0.086), Days 10–12 (3.5 ± 0.3 vs 2.6 ± 0.3; P  = 0.056), and Days 18–20 (2.1 ± 0.3 vs 1.5 ± 0.3; P  = 0.227). Duration of awake/content behavior increased over time with no significant differences detected in PH vs PH-LGG: Baseline (1.0 ± 0.5 vs 1.2 ± 0.5; P  = 0.786), Days 10–12 (1.3 ± 0.5 vs 1.6 ± 0.5; P  = 0.627), and Days 18–20 (2.1 ± 0.5 vs 2.2 ± 0.5; P  = 0.884). By Study End, only 8 (24%) in the PH and 9 (27%) in the PH-LGG group continued to cry and/or fuss ≥3 hours/day for ≥3 days/week. Conclusions: In the present pilot study, we identified a study population of infants early in life experiencing crying and fussing often associated with infantile colic. Both study formulas were well tolerated. Crying/fussiness decreased and awake/content behavior increased in both study groups over the course of the study. Funding Sources: Mead Johnson Nutrition.